Contracts for difference: The instrument of choice for the energy transition - Agnieszka Ason; Julio Dal Poz (The Oxford Institute for Energy Studies, 2024)
Contracts for Difference ('CfDs'), previously mainly known as financial hedging instruments, are increasingly seen as the method of choice for incentivising investment in clean energy technologies. In the power sector, the CfD mechanism has emerged as the preferred arrangement to provide the required revenue support and stimulate the construction of new renewable power generating facilities. Following the successful experience with renewable CfDs (in the UK and several other countries), it has been recognised that the CfD concept may be suitable for applications beyond power generation. Work is in progress, initially mainly in Europe and Asia, on CfD-based business models for clean hydrogen and carbon capture and storage ('CCS'), initially to be applied to one of these technologies but potentially evolving into multi-technology schemes. As an increasingly important support scheme to facilitate the global energy transition, CfDs will become an integral part of future energy markets in the coming years.
Keywords: 330; CCS; CfDs; Contracts for Difference; Energy Transition; Hydrogen; Renewable Energy